Measuring Youth Quality of Life in Sub-Saharan Africa Exploring the Role of Qualitative Methods - Mac-Ikemenjima, Dabesaki; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book explores the conceptualisation and measurement of youth quality of life in sub-Saharan Africa. Further, it addresses methodological questions relevant to the development of measures and gaining an understanding of youth quality of life in this region. Drawing on the data collected, it subsequently explores students' primary goals and their satisfaction with the extent of having achieved those goals. Accordingly, the book fills an important gap in the available literature on youth quality of life, and advances the role of qualitative methods in developing youth quality of life measures in sub-Saharan Africa.
Chapter 1. Youth in sub-Saharan Africa -- Chapter 2. Conceptualising and Measuring Youth QoL -- Chapter 3. The Role of Qualitative Methods in Youth QoL Research -- Chapter 4. Validating the SQOLS Measure -- Chapter 5. From Grounded Theory to Structural Equation Modelling -- Chapter 6. Policy and Practice Implications of Youth QoL Research in Africa -- Chapter 7. Conclusion.-.
Keywords: Education; Children; Developmental psychology; Sociology -- Methodology; Childhood Education; Developmental Psychology; Sociological Methods